RISK ANALYSIS OF HEALTH IN THE NEONATAL PERIOD (ON THE EXAMPLE OF NOVOKUZNETSK MATERNITY WARD OF THE CLINICAL HOSPITAL № 5) - Наталья Михайловна Жилина; Юлия Геннадьевна Шахова (The Publishing House Medicine and Enlightenment, 2018)
The aim of the research - analysis of health risks of pregnant women and newborns in the dynamics for a number of years and comparison of obstetric institutions of Novokuznetsk. Materials and methods. Signal information of the Novokuznetsk medical information and analytical center on the state of health of the population and data of maternity Department of Novokuznetsk city clinical hospital N 5 for 2009-2017 the database in the license statistical package IBM SPSS Statistics 22 is Created. A pairwise comparison of the factors in independent groups was performed using the z-criterion and the χ2 criterion. Relative indicators of perinatal mortality of full-term and premature infants in the dynamics of 2009-2017 were analyzed by Wilcoxon criterion. The significance of the trend in the dynamics was tested using the Kendall criterion. The critical level of significance p = 0.05. Results. The main risk factors of pregnancy and health of newborns in the maternity Department of the city clinical hospital N 5 in Novokuznetsk in the dynamics for 2009-2017 were revealed. It is proved that anemia, urinary tract infections, placental insufficiency, bleeding in the early stages of pregnancy, polyhydramnios rates significantly higher than the urban level. Received natural tendency of reduction of neonatal morbidity that is associated with the improvement of quality of rendering of medical aid to newborns. It is shown that full-term is a significant factor in the survival of the child in the first week of life. Conclusion. The results of the study can be used by health care managers in order to improve the work of the maternity service of the institution and the city.